A study of the role of e-commerce implementation on electronic banking development - Fatemeh Nehzat; Hamid Maleki; Abdollah Naami (Management Science Letters)
This paper presents an empirical investigation to study the role of e-commerce implementation of development of electronic banking. The study determines the effects of four factors, management knowledge, technological issues, financial and socio-economic factors on development of e-banking in city of Tehran, Iran. The study designs a questionnaire in Likert scale and distributes it among 96 randomly selected managers who work for Bank Saderat Iran. Cronbach alpha has been calculated as 0.89, which is well above the minimum acceptable level. Using Pearson correlation as well as stepwise regression technique, the study has determined that management, social and economic factors influence the most on electronic banking development.